DEVELOPMENT OF TRADITIONAL FISH PRESERVATION TECHNIQUES ON THE COASTAL COAST OF BENGKULU CITY E-BOOKLET LEARNING MEDIA USING ADDITIVES - Fira Pratiwi; Mellyta Uliyandari; Ariefa Primair Yani; Irwan Koto; Bhakti Karyadi (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
The purpose of this project is to produce an electronic booklet that junior high school science students studying additives will be able to use as a learning aid, particularly when it comes to the traditional fish preservation techniques used along Bengkulu City's shore. This research uses the Borg & Gall model which is carried out only until the fourth stage, 1) research and data collection (research and information), (2) planning, (3) developing a product design (developing an early form). a product), (4) field trials (preliminary field tests). The research instruments included observation sheets, teacher interview sheets, student readability test questionnaires and expert validation sheets. Based on the validation test results of material experts (88.75%), media experts (93.75%), and practitioners (94.53%), the research results indicate that the e-booklet on traditional fish preservation techniques on the coast of Bengkulu City is very suitable for use as an additive material learning medium for students. Students' assessment of the e-booklet as a means of learning additional material about traditional fish preservation methods on the coast of Bengkulu City showed a very good category with a percentage of 91.99%. In conclusion, the e-booklet on traditional fish preservation techniques on the coast of Bengkulu City as a learning medium for additive material is very suitable for use in learning science and additive material for class VIII SMP.